Does Relation between Energy and Economic Growth hold for all Indian States? Empirical Analysis using Hurlin-Venet Process - Arora, Rochna; Kaur, Baljit (Review of Economic Analysis, 2025)
Electricity consumption is often regarded as a precondition for economic growth and any bottleneck in its production can severely hurt the growth prospects of an economy more specifically a developing one. Representing a strong case of its value, the causal relationship between energy consumption and economic growth is addressed by extending the Granger causality framework in a heterogeneous panel setup. Exclusively four different causal behaviours are examined: Homogeneous Non-Causality (HNC), Homogeneous Causality (HC), Heterogeneous Non-Causality (HENC), and Heterogeneous Causality (HEC). Both HNC and HC hypotheses are rejected in the causality direction from Economic growth to energy consumption thereby suggesting that the panel of Indian states is not homogeneous. Following this heterogeneous causality tests (HENC and HEC) are conducted for each Indian state to check the hypothesis of causality from economic growth to energy. For 8 out of 17 Indian states strong unidirectional causality is found while for 6 other states, there is no evidence of any causality in the stated direction. The remaining 3 states show weak evidence of causality. Thus, the results are suggestive of the fact that the central government cannot dictate policies at the state level rather state needs to frame regional policies in line with the situation that suits.